2017
DOI: 10.2147/ott.s134813
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinase-9 in transforming growth factor-β1-induced epithelial–mesenchymal transition in esophageal squamous cell carcinoma

Abstract: Epithelial–mesenchymal transition (EMT) is thought to be a crucial event during the early metastasis of tumor cells. Transforming growth factor (TGF)-β1 is involved in the process of EMT in a variety of human malignancies. Matrix metalloproteinase (MMP)-9 plays an important role in tumor invasion and metastasis, and its expression is regulated by various growth factors, including TGF-β1, in different cell types. To date, the role of MMP-9 in TGF-β1-induced EMT in esophageal squamous cell carcinoma (ESCC) remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
2
35
0
1
Order By: Relevance
“…Researchers found that SMAD4 plays a tumor suppressor role in many cancers, such as gastric cancer (GC), colorectal cancer, and cholangiocarcinoma . However, a large number of research showed that SMAD4, a significant factor in the TGF‐β/SMAD4 signaling pathway, plays a crucial part in signaling into the cell membrane and can contribute to the progression of EMT, Unfortunately, The specific role of SMAD4 in TGF‐β‐induced EMT in ESCC remains understudied. We provided evidence that knocking down of SMAD4 expression could partially reverse TGF‐induced EMT progression, increases E‐Cadherin protein expression, decreases N‐Cadherin and vimentin protein expression, and inhibits the invasion and migration of EC‐1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that SMAD4 plays a tumor suppressor role in many cancers, such as gastric cancer (GC), colorectal cancer, and cholangiocarcinoma . However, a large number of research showed that SMAD4, a significant factor in the TGF‐β/SMAD4 signaling pathway, plays a crucial part in signaling into the cell membrane and can contribute to the progression of EMT, Unfortunately, The specific role of SMAD4 in TGF‐β‐induced EMT in ESCC remains understudied. We provided evidence that knocking down of SMAD4 expression could partially reverse TGF‐induced EMT progression, increases E‐Cadherin protein expression, decreases N‐Cadherin and vimentin protein expression, and inhibits the invasion and migration of EC‐1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of signaling pathways participate in the EMT process of human cancer . The superfamily of transforming growth factor‐β (TGF‐β) plays a significant part in tumorigenic as well as metastatic processes of ESCC . By ligand binding to type II receptor, the cascade of TGF‐β signaling pathway is initiated.…”
Section: Introductionmentioning
confidence: 99%
“…The MMPs are degradative enzymes that alter the surrounding extracellular membrane and allow tumor cells to migrate into the surrounding matrix (6). In addition to the ability of MMPs to remodel ECM, some of these molecules, such as MMP-3, MMP-9, MMP-14, and MMP-28, are known to induce EMT directly (4,33). Elevated expression levels of MMP-2 and MMP-9 are found in the tissue, serum, and urine of patients with bladder tumors (1, 31), a study result reported that virulent TCC is characterized by a high MMP-9:E-cadherin ratio (34).…”
mentioning
confidence: 99%
“…Our results were consistent with those findings, specifically that a high expression level of both MMP-2 and MMP-9 coupled with low level of E-cadherin and high level of Vimentin expression and this was associated significantly with aggressiveness of TCC. Several studies have shown a direct regulation of MMPs by EMT-associated transcription factors (33,35). It was recently demonstrated that transforming growth factor TGF-β1 which is one of the pivotal factors regulating EMT, can lead to an increase in the expression of MMPs, such as MMP-2 and MMP-9, in breast and oral cancers (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation